2016
DOI: 10.3928/00904481-20160523-01
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Cysts

Abstract: Splenic cysts are rare in the United States but more common in regions of the world where Echinococcus is endemic. Cysts are typically classified as true cysts or pseudocysts. True cysts can be parasitic or nonparasitic in origin, whereas most pseudocysts are a result of previous trauma. Recent recognition of features shared by true cysts and pseudocysts suggests the classification system may need to be revised. The prevalence of splenic cysts has increased secondary to the widespread use of abdominal imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
0
25
0
2
Order By: Relevance
“…Symptoms are generally correlated with size, 3 with the smallest generally being asymptomatic. [1][2][3][4][5][6] The confirmatory diagnosis is radiological. The initial imaging test is an ultrasound scan with pulse Doppler.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms are generally correlated with size, 3 with the smallest generally being asymptomatic. [1][2][3][4][5][6] The confirmatory diagnosis is radiological. The initial imaging test is an ultrasound scan with pulse Doppler.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to carefully delineate the splenic vascularization, both arterial and venous branches. [1][2][3][4][5][6][7] Less aggressive therapeutic alternatives have been described for splenic cysts. Ultrasound monitoring may be useful in simple cysts under 5 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their series of 32 cases, Robertson et al [10] found that the recidivism rate after the laparoscopic operation was 22%, but a new surgical intervention was required in only 3% of the patients. In order to reduce the risk of recurrence of the disease, it is considered necessary to remove as much of the wall of the cyst as possible [2,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the presence of epithelium that covers the lumen of the cyst, cysts are divided into primary (true) and secondary (pseudocysts). The primary ones are epithelial (epidermoid, dermoid, mesothelial) or endothelial (hemangioma, lymphangioma) [2]. Primary cysts are most commonly found in children and younger persons, comprising about 25% of all non-parasitic cysts.…”
Section: Introductionmentioning
confidence: 99%